Lighting In Pandemic Films - Shafiee, Rasmuna; Bidin, Azman (2016)
A genre recognition coincides with what a film is about through an identification of sound, mise-en-scene, dialogue and a cinematography elements. Although films are indistinctly classified of a specific genre, film elements can be a parameter to define the film belongs. A lighting which is one of the elements in mise-en-scene is known as a key to storytelling. A lighting in film unquestionably enhances the film stylistic value. Despite most genre critics argue that films will share consistent narrative patterns, however Rick Altman, Daniel Chandler, Bruce Kawin and Steve Neale have distinguished a cataloguing of similar elements approach that define a genre such as lighting. Therefore, the works of (Bordwell and Thompson, 2013) and (Pramoggiore and Wallis, 2005) are explored to identify which are applicable to genre classification to identify consistency of lighting features. This research introduces a genre for pandemic via lighting categorisation.